MANAGERIAL PERFORMANCE MODEL THROUGH DECISION MAKING AND EMOTIONAL INTELLIGENCE IN PALUTA DISTRICT - Harahap, Erwin H.; Hapzi Ali (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to determine and analyze the effect of Emotional Intelligence on Managerial Performance directly and indirectly through Decision Making. The sample in this study amounted to 44 regional device organizations leaders in Padang Lawas Utara (Paluta) District. Data analysis method using path analysis. The results of the study note that Emotional Intelligence and Decision Making simultaneously affect Managerial Performance, but partially Decision Making has a more dominant influence. The indirect effect of Emotional Intelligence on Managerial Performance through Decision Making is greater than the direct influence of Emotional Intelligence on Managerial Performance, thus Decision Making is able to be an intermediary variable for the influence of Emotional Intelligence on Managerial Performance.